A judicialização da saúde no Brasil: direito ao acesso à saúde e os requisitos usados pelos tribunais para deferimentos em pedidos na área da saúde - Knakeivicz, Hellen Schmidt (My University, 2025)
The present work aims to analyze the judicialization of health in Brazil, entering into the right to access to health and the right to access to the judiciary, observing the requirements used by the country's courts to grant requests in this scope, in addition to seeing the legal effects resulting from this excess . According to a survey carried out by the National Council of Justice (2019), there was an increase of 130% in the filing of lawsuits in the first instance and, in the second instance, an increase of 85% in the number of case distribution was found, both related to health. Based on this, the examination of the consequences of this intervention by the Judiciary is extremely relevant, as it is a problem that persists and, according to these surveys, has been gradually increasing. Thus, based on the decisions and materials collected, it was concluded that the limits of the intervention of the Judiciary in actions that are the responsibility of the Executive Power have been placed on the agenda, so much so that, as analyzed in the decisions, the courts use requirements for granting of requests in this area, such as: the patient's right to access to health; the competence of public entities, because if the resources to provide treatment are insufficient, the Union must be included in the passive pole and, if the therapy is in public policies, the Union must be included for the purpose of protecting interest; if the treatment is contemplated by state policies and, if not, it must be analyzed if it is registered with ANVISA or if it is something experimental; in cases of surgery, if the patient is on the waiting list and the urgency, so that there is a break in the waiting list. That said, it appears that there must be a balance between the performance of these powers, in order to guarantee the right to access to health, respecting the uniqueness of each case and without causing budgetary damage to the State. [resumo fornecido pelo autor]
O presente trabalho visa analisar a judicialização da saúde no Brasil, adentrando ao direito ao acesso à saúde e o direito ao acesso ao judiciário, observando os requisitos usados pelos tribunais do país para deferir pedidos neste âmbito, além de ver os efeitos jurídicos decorrentes deste excesso. De acordo pesquisa feita pelo Conselho Nacional de Justiça (2019), constatou-se um aumento de 130% em ajuizamentos de processos em primeira instância e, em segunda instância, apurou-se um acréscimo de 85% do número de distribuição de processos, ambos relacionados à área da saúde. A partir disto, o exame das consequências desta intervenção do Poder Judiciário é de extrema relevância, porquanto trata-se de um problema que persiste e, conforme estas pesquisas, vem aumentando gradualmente. Assim, com base nas decisões e materiais colhidos, concluiu-se que vem sendo colocado em pauta os limites da intervenção do Poder Judiciário em atuações que estão a cargo do Poder Executivo, tanto que, conforme analisado nas decisões, os tribunais utilizam de requisitos para deferimentos nos pedidos nesta área, tais como: o direito do paciente ao acesso à saúde; a competência dos entes públicos, pois caso os recursos para fornecer o tratamento sejam insuficientes, a União deve ser incluída no polo passivo e, caso a terapêutica esteja nas políticas públicas, a União deve ser incluída para fins de proteção de interesse; se o tratamento é contemplado por políticas estatais e, se não for, deve ser analisado se possui registro na ANVISA ou se trata de algo experimental; em casos de cirurgia, se o paciente se encontra na lista de espera e a urgência, para que haja a quebra na lista de espera. Isso posto, verifica-se que deve haver um equilíbrio entre a atuação destes poderes, a fim de que garantam o direito ao acesso à saúde, respeitando a singularidade de cada caso e sem trazer danos orçamentários ao Estado. [resumo fornecido pelo autor]
Keywords: Acesso aos serviços de saúde - Aspectos jurídicos; Direito à saúde - Brasil; Orçamento - Legislação - Saúde; Política pública - Saúde